산업용 원심블로어 수치해석을 위한 수치모델 평가 - 이종성(Jong Sung Lee); 장춘만(Choon Man Jang) (한국수소 및 신에너지학회 논문집, 2012)
The present study represents the effects of boundary condition on the performance of a centrifugal blower at the interference plane between rotational and stationary domains using three dimensional compressible Navier-Stocks equations. Two boundary conditions, frozen-rotor and stage, are compared to analyze the blower performance. Installation angle between the cutoff of a volute casing and a impeller blade is also introduced to evaluate the blower performance and to understand the internal flow inside the blower. Throughout numerical simulation, it is found that the frozen rotor interface method at the interference plane represents well the variations of flow field inside the blower compared to stage interface method. However, pressure has maximum two percent error according to the installation angles while pressure is almost constant for the stage interface method. And stage interface method can relatively well predict the blower performance. Detailed internal flows of the centrifugal blower are compared and analyzed by numerical simulation.